Development of algorithms for high performance digital image processing with applications to medical imaging - Zhang, Cishen (2008)
The objectives of this Start Up Grant Project “Development of Algorithms for High Performance Digital Image Processing with Applications to Medical Imaging” are to extend and apply the recent research results in two-dimensional system filtering and digital image processing to the development of methods and algorithms in medical imaging. We have conducted research in two areas of medical imaging which are ultrasound imaging and computed tomography (CT) imaging. In ultrasound imaging, we introduce a new tissue model where the inclusion of more realistic physical analysis in the received pulse-echo pressure field shows that there are two different natures of noise sources existing in the received ultrasound RF echo. One is inherent in the tissue response and the other is the measurement noise. A desirable ultrasound image can be obtained only when effects of both kinds of noise are suppressed.